RANCANGAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (SMK3) BERBASIS OHSAS 18001-2007 DAN SISTEM INFORMASI WEB PORTAL STUDI KASUS DI DI KSO PERTAMINA EP - BBP - Yuli Nurcahyo (JURNAL TEKNIK INDUSTRI, 2014)
To anticipate and decrease the total amount of work accidents and occupational ilness,the Indonesian government requires that every company has an obligation to implement theOccupational Health and Safety Management System (OHS MS). In this regard, KSO PertaminaEP-BBP begin drafting a strategic step in reducing, managing and avoiding losses caused byworkplace accidents began compiling Occupational Health and Safety Management System(OHS MS).The results of the study found the gap between the requirements of OHSAS 18001-2007standard with OHS MS application in the enterprise. From the results of the evaluation of thedata gap analysis of OHS conducted , then obtained the average value: 2.18 with medium-scalegap (partially complied with the requirements). This is due to the absence of the OccupationalHealth and Safety Management System designed effectively, and integrated.The design of OHS MS base on OHSAS 18001-2007 and the Information Systems madein the form of a web portal which was named Benakat Hebat Tanpa Insiden (KATAHATI). Theresults of the evaluation conducted found an average value of 3.06 (low gap or need toconsistently adhere to the requirements), when compared with the previous OHS MS, then thereis an increase in the average value: 0.88 of every element of the requirements of OHSAS 18001-2007. From the comparison of the old system with a new one, found an increase in complianceand implementation and improvements of OHS MS in the company.